Farming Analysis Of The Juai-Pumpkin In The Juai Village, Balangan, South Kalimantan - J, Prihananto; Kusumawardani, N.D.; Handayawati, H. S. (Program Pascasarjana Universitas Brawijaya, 2012)
This research was conducted in the village of Juai, Balangan South Kalimantan. The goal of research to analyze the revenue, income and profits of farming Pumpkins Juai during one period of cropping. This study used a survey method with the further observation techniques, while sampling is carried out by census, which is as many as 45 farmer. Results show that the magnitude of the costs used in the farming of pumpkins is an explicit cost of Rp 2.335.815, implicit costs of Rp 354.594 and the total average cost of Rp 2.690.409. The fruits produced by a farmer on average 1.150 kg, the fruit price per kg is varied between Rp 5.750 to Rp 7.000, so the farming revenue of Rp 7.380.555. Earned income of a farmer on average about Rp. 5.044.740. The average profit obtained a farmer about Rp 4.690.145 in a single production process; with a value of R/C = 2.74.Keywords: Farming, revenue, income, profit.